Exploring the gynecologist-patient relationship in hospitals of Islamabad and Rawalpindi, Pakistan - Zubair, Asim; Fatima, Sonia; Ying, Haihua; Ahmad, Faizan (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2025)
The research was conducted on “Gynecologist-patient relationship: A case study of hospitals in twin cities.” Pakistan. This study examined the relationship between doctors and patients. Specifically, a Gynecologist’s attitude towards their respective patients. The primary objective of this study was to investigate the relationship between gynecologists and hospital patients. The researcher employed a qualitative study to investigate the attitudes of gynecologists. For data collection, a sample of 15 respondents was selected, and one in-depth interview was conducted with pregnant patients (female). The researcher used a snowball and purposive sampling techniques to collect data. According to the results, patients mostly prefer female gynecologists over male gynecologists because they feel shy and hesitate to talk and discuss issues with male gynecologists. They share their health-related problems and discuss them freely and frankly with female gynecologists. Most respondents also prefer being treated in private hospitals compared to public hospitals, despite the higher fees charged by private hospitals. However, they do not want to take risks, as this can create complications during the delivery phase. The current research also shows that professional gynecologists prefer not to treat their family members because they are emotionally attached to them.